"I Was Surprised by Their Culture": Emotional Antecedents for Indonesian English Teachers in Thailand - Haryadi, Didit; Wilang, Jeffrey Dawala (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Emotions are pivotal in shaping teaching behavior and quality, especially in the English Language Teaching (ELT) context. While prior research has largely focused on teachers within their home environments, the emotional experiences of non-local teachers, such as Indonesian English teachers in Thailand, remain underexplored. This study investigates the antecedents of these teachers' emotional experiences, considering the unique challenges of language barriers and cultural differences. Using semi-structured interviews with 10 Indonesian English teachers in Thai elementary and secondary schools, the researchers conducted a thematic analysis to identify key emotional triggers. Our findings reveal that student-related factors, such as positive interactions and academic achievements, evoke happiness, pride, and satisfaction. Conversely, negative behaviors and comprehension issues lead to frustration, annoyance, and stress. Teacher-related factors, including teaching proficiency, significantly influence their emotional landscape. Additionally, other factors like collegial relationships, school culture, workload, and parental involvement further shape their emotional experiences. The implications of this study are critical for educational psychology, teacher education, and communication within international contexts. For educators, engaging in cultural adaptation and continuous professional development is essential for enhancing emotional resilience and teaching effectiveness. Schools should aim to create inclusive environments that support non-local teachers and offer tailored professional development. Training programs should focus on cultural competence and effective communication strategies to better prepare teachers for international teaching assignments.